Looking for the origin of life in cosmochemistry: Asteroids and their carbon-rich meteorites - Sandra Pizzarello (Mètode Science Studies Journal: Annual Review)
Carbonaceous chondrite meteorites are carbon-containing fragments of primitive asteroids that have offered the only samples available to date giving insights into chemical evolution in laboratory analyses. Their study has revealed that abundant organic chemistry came to be in the Solar System ahead of terrestrial life and, by the input of these meteorites and comets, might have aided in the origin of our planet’s biochemistry.